The two linear equations represented in system A as :
3 x + 2 y =3 -------(1)
- 2 x - 8 y = -1 ------(2)
(1) × 2 + (2) × 3 gives
⇒ 6 x + 4 y - 6 x - 24 y = 6 -3
⇒ - 20 y = 3
⇒ y =
Putting the value of y in equation (1), we get
Two linear equation represented in system B is:
3. -x - 14 y =1
4. - 2 x - 8 y = -1
-2 ×Equation (3) + Equation (4)=
2 x +28 y- 2 x - 8 y= -2 -1
⇒ 20 y = -3
⇒y =
Putting the value of y in equation (3),we get
As Two system , that is system (A) and System (B) has same solution.
By looking at all the options , i found that Option (D) is correct. The two system will have the same solution because the first equation of System B is obtained by adding the first equation of System A to 2 times the second equation of System A.